Pemetaan Penelitian Pada Bidang Budaya Di Indonesia Pada Scopus Menggunakan Vosviewer - Yunus Winoto; Dhila Sri Nuraeni (Fakultas Adab dan Humaniora UIN Raden Fatah, 2023)
ABSTRACT Culture is a habit of a society that is continuous and carried out from generation to generation. As an archipelagic country, Indonesia has a rich culture that creates a multicultural society. This diversity is a highlight for researchers to examine the cultural sector in Indonesia. Thus were born various scientific works in the field of culture in Indonesia with different focuses. This study aims to determine the mapping of cultural research in Indonesia using VosViewer and the data taken is scientific papers from the journal Scopus. The results of this study show that the field of culture in Indonesia visualizes that there are two klasters that are interconnected with one another. With the many publications in 2020 and the topics that have the most scientific work on traditional topics.